The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1590/s1516-35982010000200003
|View full text |Cite
|
Sign up to set email alerts
|

Ingestive behavior and displacement patterns of beef heifers on Italian ryegrass pasture

Abstract: -The effect of supplementation on ingestive behavior and displacement patterns of beef heifers grazing on Italian ryegrass (Lolium multiflorum Lam.) pasture was evaluated. The grazing method was continuous with variable stocking rate. The experimental design was completely randomized with repeated measures on time. The supplement utilized was a commercial ration (17% CP, 21.4% NDF), daily supplied at 2 pm, in the proportion of 1% of body weight. The evaluations were made through visual observations, in four co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
5
0
3
Order By: Relevance
“…Glienke et al (2010) found lower grazing time for supplemented animals, corresponding to 1% BW of supplement (7.5 h/d), in comparison with non-supplemented animals (9.0 h/d). Nonetheless, in this study, grazing time was not affected by supplementation, possibility because the supplement intake was low.…”
Section: Discussionmentioning
confidence: 76%
“…Glienke et al (2010) found lower grazing time for supplemented animals, corresponding to 1% BW of supplement (7.5 h/d), in comparison with non-supplemented animals (9.0 h/d). Nonetheless, in this study, grazing time was not affected by supplementation, possibility because the supplement intake was low.…”
Section: Discussionmentioning
confidence: 76%
“…Silva et al (2006) Na literatura sobre comportamento ingestivo em pastejo (BREMM et al, 2008;ÍTAVO et al, 2008;FREITAS et al, 2010;GLIENKE et al, 2010;JOCHIMS et al, 2010;MENDES et al, 2010;MISSIO et al, 2010), verificou-se que essas quatro variáveis (MMB, TBo, BOL e MMnd) são as únicas utilizadas nas avaliações dos aspectos do comportamento ingestivo de ruminantes, esse resultado demonstra que não há necessidade de avaliação em dois turnos (manhã e tarde), sendo que somente uma avaliação, tanto pela manhã quanto pela tarde, apresenta resultados semelhantes.…”
Section: Resultsunclassified
“…Já Glienke et al (2010), avaliando o comportamento ingestivo de bezerras de corte, encontraram maiores massa de bocados para maiores níveis de suplementação. No entanto, no presente estudo, não houve diferenças significativas entre NC e o controle entre os animais que saíram do período de restrição (menor nível de concentrado) para a realimentação (maior nível de concentrado).…”
Section: Resultsunclassified